Teachers' Information and Communication Technologies (ICT) using achievements and attitudes towards ICT - (:unkn) unknown (HACETTEPE UNIV, 2008)
Within MEB's criteria on General Competencies for Teaching Profession, teachers are expected to be individuals, who are able to use technology and be a model for students in that respect. This study was conducted to determine level of teachers' success in using Information and Communication Technologies (ICT) and to examine their attitudes towards ICT. The study was conducted using survey method and research population consisted of 163 teachers. Firstly, teachers' ICT using achievements and attitude towards ICT were determined using Attitude Towards ICT Scale and an examination on ICT use. Then relations between teachers' relevant attitudes and using achievements were studied. Study findings suggest there are considerable deficiencies in teachers' use of ICT. It was found that teachers' general attitude towards use of ICT in education was positive; but they thought using ICT in crowded classrooms would increase their responsibilities. A high level of positive relation was found between teachers' ICT using achievements and attitudes towards ICT. Findings of the study also emphasize requirement of re-arrangement of computer course curriculum used at faculties of education and MEB's in-service training programs regarding both contents and methods used.
Keywords: ICT using achievement; attitudes towards ICT